Synthesis of SiO₂ matrices doped with some inorganic compounds - Blank, T.A.; Ganina, I.I.; Malyukin, Yu.V.; Eksperiandova, L.P. (Functional Materials, 2009)
The properties of silicon dioxide xerogels doped with salts and nanoparticles of inorganic compounds have been studied. Optimization of the synthesis and annealing conditions of SiO₂ matrices made it possible to increase essentially the microhardness of the doped samples. Using the aquametry technique, there was established the distribution mechanism of the of titanium oxide nanoparticles in the xerogel matrix intended to develop the new generation of luminescent materials. To obtain a moisture-resistant material, with increased service life, it has been proposed to dope the xerogel matrices with titanium oxide nanoparticles or to treat the undoped matrices with nitrocellulose lacquer.